Arthroscopic Volar Capsuloligamentous Reattachment and Reinforcement to Bone - Corella, Fernando; Ocampos, Montserrat; Laredo, Rafeal; Tabuenca, José; Larrainzar-Garijo, Ricardo (Journal of Wrist Surgery, 2023)
Background: Injuries of the volar ligaments of the wrist are not uncommon, but their arthroscopic treatment presents a significant challenge. The objective of this paper is to introduce a technique for reattaching (in acute injuries) or reinforcing (in chronic injuries) various volar wrist ligaments to the bone, using standard wrist arthroscopic dorsal and volar portals.Methods: There are three common steps for all the arthroscopic volar capsuloligamentous reattachments or reinforcementsStep 1 – Volar Portal Establishment: volar radial, volar ulnar and volar central portals are used depending on which structure needs to be reattached or reinforced.Step 2 – Anchor Placement: the anchor is positioned at the site where the ligament has been detached.Step 3 – Capsuloligamentous Suture and Knotting: a knot pusher is introduced inside the joint from the dorsal portal and advanced inside the volar portal where the threads of the anchor are located. The knot pusher is loaded with the threads and retrieved to the dorsal portal. A 16G Abbocath, loaded with a loop is used to pierce the volar ligaments. The loop of the Abbocath is captured from the dorsal portal and loaded with the threads. Both threads are taken to the volar portal and knotted after releasing the traction. This way the knot is placed out of the wrist and the ligaments are reattached or reinforced to the bone.Result: This technique has been used to reinforce and reattach the scapholunate and lunotriquetral ligaments and to reattach the radiocarpal ligaments and the Poirier space. Since this procedure has been performed in various conditions and in conjunction with other ligament treatments (such as perilunate injuries, carpal bone fractures, distal radius fractures, and reinforcement or reattachment of the dorsal portions of intrinsic ligaments), specific results are not presented.Conclusions: The described technique enables the reattachment and reinforcement of most volar ligaments to the bone using standard wrist arthroscopic portals. It can be performed in conjunction with the treatment of the dorsal portion of intrinsic ligaments or other wrist injuries.
Keywords: volar capsuloligamentous suture; wrist arthroscopy; perilunate injuries; scapholunate injury; lunotriquetral injury